2022
DOI: 10.1177/15353702211070290
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinflammation after anti-SARS-CoV-2 mRNA/DNA vaccines successfully treated with anakinra: Case series and literature review

Abstract: The current SARS-CoV-2 pandemic diffused worldwide has encouraged the rapid development of vaccines to counter the spread of the virus. At present in Italy, 75.01% of the population completed the vaccination course (AIFA.gov.it) and very few adverse events have been recorded by now. Side-effects related to a theoretical over-reaction of the immune system in response to vaccines administration have been described, and the possibility that an autoimmune or a hyperinflammatory condition may occur was recently obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Though rare systemic inflammatory and immune-mediated adverse events have been reported following SARS-CoV-2 immunizations [ 8 , 9 , 10 , 11 ], we report here the first case of biopsy-confirmed iMCD that appears to be associated with SARS-CoV-2 immunizations. The clinical picture of our patient fulfilled the proposed consensus criteria for iMCD [ 7 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Though rare systemic inflammatory and immune-mediated adverse events have been reported following SARS-CoV-2 immunizations [ 8 , 9 , 10 , 11 ], we report here the first case of biopsy-confirmed iMCD that appears to be associated with SARS-CoV-2 immunizations. The clinical picture of our patient fulfilled the proposed consensus criteria for iMCD [ 7 ].…”
Section: Discussionmentioning
confidence: 73%
“…Of the 11 proposed minor criteria, 6 were present, including elevated CRP, thrombocytopenia, hypoalbuminemia, constitutional symptoms, hepatosplenomegaly and effusions. The patient also fulfilled the proposed international definition for the TAFRO syndrome, which is considered as an aggressive subtype of iMCD, requiring four clinical criteria (thrombocytopenia, anasarca, fever/hyperinflammatory status, organomegaly), renal dysfunction or characteristic bone marrow findings [ 12 ] and a lymph node with features consistent with iMCD [ 8 ]. Of note, reticulin fibrosis in the bone marrow was mild in our case.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in our study reported common and mild side effects like pain at the site of vaccination, headache or fatigue, and in rare cases fever, which were temporary and disappeared after one day. Severe hyper-inflammatory reactions are rare but have also been reported after inoculation with mRNA and DNA vaccines against COVID-19 [ 50 ]. As abnormal cytokine concentrations are the driving factor behind hyper-inflammatory reactions, Arunchalam et al [ 51 ] investigated cytokine titers following BT vaccination and found that especially IFNγ was increased after the second inoculation with BT.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine concentrations were reduced back to normal ranges two days after the inoculation, suggesting that mRNA- and vector-based COVID-19 vaccines cause a temporal, short-lived inflammatory immune reaction in healthy participants. In case of hyper-inflammatory reactions due to COVID-19 vaccination, treatment with the IL1 receptor antagonist Anakinra was able to restrain the overshooting immune response to the vaccination [ 50 ]. COVID-19 vaccination has been associated with adverse reactions in response to certain treatments, e.g., dermal fillers, like hyaluronic acid, polymethyl-methacrylate and fluid silicone, in the facial region [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, there are also several reports of severe systemic inflammatory symptoms occurring after COVID‐19 vaccination, such as arthralgias, fever and rashes, that were successfully treated with IL‐1 antagonists. 7 While these reactions may be similar in severity to drug‐induced hypersensitivity syndrome, the shorter latency of a few days from vaccination to symptom onset is a helpful differentiating feature. The successful treatment with IL‐1 antagonists indicates over‐reactivity of the innate immunity as the underlying pathology, rather than allergic reactions which are mediated by the adaptive immunity.…”
mentioning
confidence: 99%